Pengalaman Orang Tua terhadap Pola Asuh Anak Berkebutuhan Khusus - Sari, Ulfa; Afifah, Zahra; Daulay, Zil Rahmi; Cahyati, Eka; Lasmita, Dea; Rahmita, Ewi; Yuris, Evicenna (EL-EMIR Institute, 2025)
This study aims to explore in depth the experiences of parents in implementing parenting strategies for children with special needs through a literature review. Children with special needs (CWSN) are those who require special attention, approaches, and parenting strategies that differ from those applied to typically developing children due to differences or limitations in physical, mental, social, or emotional aspects. This study was conducted by reviewing various scholarly sources, including journals, books, and relevant articles. The findings indicate that parents’ experiences in raising CWSN are highly varied, depending on the type of the child’s needs, the parents’ level of understanding, socioeconomic background, and the availability of social support. Challenges commonly faced include emotional stress, social stigma, and limited access to services. However, the study also revealed various forms of parental resilience, such as adaptability, proactive learning, and the formation of support communities. This research is expected to provide broader insights for educators, counselors, and policymakers in designing interventions that holistically support families of children with special needs.